The impact of perceived organizational support and proactive personality on affective commitment: mediating role of prosocial motivation - Ullah, Ihsan; Elahi, Natasha Saman; Abid, Ghulam; Butt, Matti Ullah (Business, Management and Economics Engineering, 2020)
Purpose – The main objective of this study is to examine the effect of perceived organizational support and proactive personality on prosocial motivation. Furthermore, it looks upon the influence of prosocial motivation on affective commitment. The indirect effect of perceived organizational support and proactive personality on affective commitment through prosocial motivation is also examined.Research methodology – The self-administered survey questionnaires are utilised for collecting the data from the service sector employees. Data were analyzed by using Process Macros on an actual sample of 221.Findings – Results indicate that perceived organizational support and proactive personality are the drivers of prosocial motivation. Likewise, prosocial motivation is positively associated with affective commitment. Besides, the indirect effect of perceived organizational support and proactive personality on affective commitment through prosocial motivation is significant.Research limitations – This study is conducted in the specific culture and the organizational context of Pakistan (Lahore). Data of all study variables are collected from the employees (single source) and at one point in time.Practical implications – The study findings suggested that organizations should always provide support to their employees that encourage them to show more desire to help their colleagues in the working environment and fosters their commitment towards their organization.Originality/Value – It is the first study that examines the indirect impact of POS and proactive personality on affective commitment via prosocial motivation.